The (im)possibility of feminist critique in authoritarianism: Revisiting Western knowledge-transfer in Russia and Serbia - Bias, L (2020)
This thesis proposes a critique of the critique of transnational feminism in post-communist Europe. The critique of transnational feminism asserts that the process is, in essence, a unilateral knowledge-transfer, and as such functions as one among many exercises of Othering the West has employed vis-à-vis its Semi-Other since the fall of communism. Using case studies of Russia and Serbia, this research challenges this argument from three angles.